2015
DOI: 10.13189/mst.2015.030101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Vegetable Oil Based Cutting Fluids with Extreme Pressure Additive in Machining of AISI 1040 Steel

Abstract: The application of conventional cutting fluids in machining operations is harmful and not eco-friendly. In this context, the present work focuses on environmental friendly cutting fluids such as vegetable oil based cutting fluids (VBCFs). The objective of this work is to determine the influence of vegetable oil based cutting fluids (sesame and coconut oil) with extreme pressure (EP) additive on machining performance. Cutting forces, cutting tool temperature, tool flank wear and surface roughness are measured d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…[5] compared the effects of vegetable oil and industrial emulsion on the turning process of stainless steel and specified that natural oils had higher lubricating properties which affected the reduction of surface roughness. Kumar et al [6] studied the effect of vegetable oils with the addition of extreme pressure additives on cutting force, temperature, tool wear and surface roughness during turning of AISI 1040 steel.…”
Section: Review Of Modern Information Sources On the Subject Of The Papermentioning
confidence: 99%
“…[5] compared the effects of vegetable oil and industrial emulsion on the turning process of stainless steel and specified that natural oils had higher lubricating properties which affected the reduction of surface roughness. Kumar et al [6] studied the effect of vegetable oils with the addition of extreme pressure additives on cutting force, temperature, tool wear and surface roughness during turning of AISI 1040 steel.…”
Section: Review Of Modern Information Sources On the Subject Of The Papermentioning
confidence: 99%
“…Additives can form sacrificial films, which could be worn away during tribological contact. Thus, additive-fortified films could offer greater resistance and support the greater loads [11]. Prior work showed that the high molecular polymer additives could help to increase the average drop size of the cutting fluids, providing higher machining production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sesame and coconut oil, soybean oil, sunflower oil, and canola oil may be used alternatively as cutting fluids. [10][11][12] The use of waste palm oil as a bio-lubricant and the increase in the use of vegetable oil-based fluids during metalworking have gained importance as these lubricants have environmentally efficient and effective performance. [13][14][15] As a result, the search for alternative, sustainable, and biodegradable products has become more necessary.…”
Section: Introductionmentioning
confidence: 99%